Plant Regeneration from Protocorm Like Body (PLB) derived Callus of Dendrobium barbatulum Lindl. (Plant Tissue Culture and Biotechnology, 2020)
In vitro regenerative potential of protocorm like bodies (PLBs) of Dendrobium barbatulum were assessed. The formation of secondary PLBs from the primary PLBs that formed from the callus, it is derived from a few larger injured protocorm like bodies. The injured larger PLBs were cultured on half strength MS supplemented with different concentrations of BAP (0.32, 1.62, 3.23 and 16.15 μM), Zn (0.46, 2.28, 4.56 and 22.80 μM) and Kn (0.47, 2.33, 4.65 and 23.25 μM). The highest percentage of secondary PLBs (66.33%) were obtained on half strength MS medium supplemented with BAP 3.23 μM, after 5 weeks of culture. Then these clumps of PLBs were subcultured on half strength MS fortified with coconut water (CW), cane juice (CJ), peptone (P) and casein hydrolysate (CH) for regeneration. Among the complex organic additives 20% CW and 2.0 g/l P to half strength MS resulted in the development of plantlet 78.31 and 62.60%, respectively. Well developed plantlets were successfully acclimatized in the community pots having brick pieces, charcoal, decaying litter and coconut husk (1 : 1 : 1 : 1) gave maximum survival rate of 87.03%.Plant Tissue Cult. & Biotech. 30(2): 243-252, 2020 (December)